Analisis Iklan Politik Pasangan Budi Agis pada Pemilu Walikota dan wakil Walikota Kota Serang Tahun 2024 - satibi, moehamad; Suryasuciramdhan, Arfian; Damanik, Agnestesia Maria; Utami, Tri; Permana, Mutiara (JOURNAL OF SCIENTIFIC COMMUNICATION (JSC), 2025)
Political advertising is one of the efforts to "market" themselves and political messages from candidates. As a candidate, Budi Rustandi (Budi) carries out propaganda by advertising with the aim of gaining power in Serang City in collaboration with Nur Agis Aulia (Agis). The purpose of the study in this article is to explain how the political advertisements pair that were broadcast in the mass media in Banten during the 2024 Serang Mayor and Deputy Mayor election succeeded in becoming a reliable strategy in achieving the goal of winning and being elected as Mayor and Deputy Mayor of Serang for the 2024-2029 period. This study uses a descriptive-qualitative method, focusing research on the mass media advertisements of the Budi Agis pair accompanied by analysis using the concept of political communication. The results show that the political advertisements distributed by Budi-Agis have succeeded in forming a positive image. With political advertisements, they raise public awareness of their existence in the world of politics. In addition, Budi Agis' political advertisement also aims to strengthen the loyalty of members and sympathizers of the Gerindra Party and the Prosperous Justice Party (PKS) towards them while inviting non-party communities to vote for them.